Enhancement of rapid object process for embedded system (ROPES) to support pattern oriented development - Isa, Mohd. Adham (2009)
The complexity of Embedded Real Time (ERT) software development represents a challenging of analysing, designing and building ERT software. From this standpoint, the complexity of ERT software development means a challenging to adapt all ERT software requirements such as timing and resource constraints into its software lifecycle. Against these claims, a wide range of software development methodologies have been devised such as patterns. Patterns codify an effective solution for recurring problems that allows software engineers to reuse. By applying patterns into ERT software development, the complexity of ERT software development can be decreased and at the same time promote high degree of reuse through software patterns. In this project, the integrated Rapid Object Process for Embedded System (ROPES) and Pattern-oriented Analysis and Design (POAD) methodology has been developed to represent a promising way to build ERT software with software patterns reuse. To make the integrated methodology more compelling and confirm the rules of patterns oriented modelling, the integrated ROPES and POAD metamodel has been developed. The aim of the integrated metamodel is to conform the correctness of the integrated methodology modelling rules in term of pattern uses. In addition, the integrated ROPES and POAD software process also has been built as the continuity to describe concrete integrated software development process. To verify the correctness of the integrated metamodel, the mapping process of Meta-Object Facility (MOF) using graph theory has been conducted. The results of implementing the integrated metamodel and software process for Feedback Control System (FCS) shows that the complexity of ERT software development has been decreased besides promote software patterns reuse.